Hubungan Tingkat Kontrol Diri dengan Perilaku Konsumtif pada Remaja Penggemar Kpop di Komunitas ONCE Medan - Valen Bogenvile; Tania Rosandi; Doharma Indawaty Siregar; Ria Wulandari Siagian; Yunika Maria Sinurat; Achmad Irvan Dwi Putra (Mahesa Research Center, 2022)
This study was intended to find out the relationship between self-control and Consumtive behavior in teenagers k-pop fans in the ONCE community Medan. The research subject used in this study were 100 teenagers k-pop fans in the ONCE community at medan using purposive sampling technique. This study used quantitative method, data collection used 40-item of self-control scale and 40-item of psychological consumtive behavior scale. The assumption test consisted of normality test and linearity test. The data were analyzed using Pearson Product Moment correlation test with the SPSS version 25.0 for Windows. The data analysis showed a negative correlation between between self-control and consumtive behavior in teenagers k-pop fans in the ONCE community Medan with pearson product moment coefficient of correlation r= -0,384 dan sig sebesar 0,000 (p <0,05). These results indicate that the research hypothesis is accepted. Meanwhile, the effective contribution of self-control in influencing consumptive behavior is 14.7 percent. From these results, it is concluded that the hypothesis, which stated that there is a negative relationship between selfcontrol and consumtive behavior is acceptable.